Circulating extracellular miR-22, miR-155, and miR-365 as candidate biomarkers to assess transport-related stress in turkeys. (13th January 2016) - Lecchi, C.; Marques, A. T.; Redegalli, M.; Meani, S.; Vinco, L. J.; Bronzo, V.; Ceciliani, F.
Abstract : MicroRNA (miRNA) have been identified in circulating blood and might have the potential to be used as biomarkers for several pathophysiological conditions. To identify miRNA that are altered following stress events, turkeys ( Meleagris gallopavo ) were subjected to 2 h of road transportation. The expression levels of five circulating miRNA, namely miR-22, miR-155-5p, miR-181a-3p, miR-204 and miR-365-3p, were detected and assessed by quantitative polymerase chain reaction using TaqMan ® probes, as potential biomarkers of stress. The areas under the receiver operating characteristic curves were then used to evaluate the diagnostic performance of miRNA. A panel of three stress-responsive miRNA, miR-22, miR-155 and miR-365 were identified; their expression levels were significantly higher after road transportation and the area under the curve (AUC) were 0.763, 0.71 and 0.704, respectively. Combining the three miRNA a specificity similar to the one found for the three miRNA separately was found. The AUC of the weighted average of the three miRNA was 0.763. This preliminary study suggests that the expression levels of circulating miR-22, miR-155 and miR-365 are increased during transport-related stress and that they may have diagnostic value to discriminate between stressed- and unstressed animals.